On the means of bioproduction : bioinformatics and how to make knowledge in a high-throughput genomics laboratory - Stevens, Hallam (2013)
Accounts of ‘biocapital’ abound in studies of the contemporary biosciences. However, these have tended to pay attention to the use and consumption of biological knowledge rather than the means and conditions of the production of data. This paper draws on an ethnographic account of a high-throughput genomics laboratory (the Eli and Edythe L. Broad Institute, Cambridge MA) to show how the means through which biological data is produced exerts a determinative effect on the kind of knowledge that is generated by the laboratory. High-speed, high-volume, high-efficiency production of data requires the high-throughput consumption of data by statistical and computational techniques. These techniques, in turn, generate general, broad-scale accounts of biological systems, rather than particular knowledge about individual genes or biological components. This cycle of production and consumption is described as ‘bioinformatics’ in order to indicate the centrality of computers and computing to the knowledge production process in contemporary biology.